Estimating energy savings and greenhouse gas emission reductions from energy rating and disclosure policies - Uriarte Cáceres, Fátima (2018)
The purpose of this paper is to estimate the energy savings and greenhouse gas emission reductions from energy rating and disclosure policies in New York City. During the first six year of the policy, the City saw a cumulative energy savings of 10.8% and cumulative GHG reductions of 8.5%. However, these gross changes cannot necessarily be attributed to the benchmarking and transparency policies. In order to estimate the “counterfactual” scenario – what would have happened if the policy was not implemented, we use a combination of Difference-in-Difference Estimation and Propensity Score Matching. Based on this model, we conclude that the disclosure of Energy Star Scores to the public did not have a significant effect on energy savings and GHG emissions reductions for multifamily buildings.